Social, Cultural, and Environmental Impact to The Existence of Religious Tourist Site Dian Al-Mahri Depok Jawa Barat - Siti Marti'ah; Berta Dian Theodora (Karsa: Journal of Social and Islamic Culture, 2017)
The phenomenon that occurred in some cities shows that the mosque has many additional functions besides the means of worship, such as a place of education and other social activities. Dian Al-mahri Mosque has been functioned widely and gives impact to the community. The impact of tourism can be divided into positive and negative. The purpose of this study is to know the impact from existence of Kubah Emas Mosque (Dian Al-Mahri Mosque) as tourism site in social, culture and environment that are happened in people in Meruyung area. The descriptive qualitative method was used in this study, data collect used observation, questioner, related documents and from key informant which was the urban village head of Meruyung. The research result show social impacts that were felt by people around Meruyung as the spiritual feeling so they are still istiqomah, it was proven by people who came for Hadits study, istighotsah and tausiyah as well as Dakwah. There are a lot of tourists that come by using vehicle, it is impacted directly to the environment, because there are a lot of emissions as well. It makes air pollution and also the traffic around that area. Another impact is garbage from the existence of this tourist site impacts the environment. It is known that the committee of Dian Al- Mahri Mosque have minimalized the negative impacts that are possibly happened. For example, there is a garden as neutralizer of air pollution from the emissions of vehicles and they also forbid the street seller come into the mosque area to make less garbages.Copyright (c) 2017 by KARSA. All right reservedDOI: 10.19105/karsa.v25i2.1171